Correlation and genetic analysis of seed shell thickness and yield factors in Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) - Li, Chunhua (Breed Sci, 2019)
In order to solve the difficult problem of the outer shell covering in the processing of Tartary buckwheat, we conducted a genetic analysis in segregating F(2) and F(3) populations derived from a hybrid between ‘Yunqiao No. 1’ and ‘Rice buckwheat’, and the F(3) population was used to analyze the phenotypic and genetic correlation among the traits. The results showed that the variety with a value of trait for seed shell thickness over 0.20 mm is a hard-shelled type (The thick shell type = seed shell rate > 20%), and that with a value of trait for seed shell thickness below 0.15 mm is a easily-shelled type (The thin shell type = seed shell rate < 20%), while that with a value of trait for seed shell thickness ranging from 0.15 mm to 0.20 mm is a hard-shelled type or easily-shelled type. In addition, alleles for traits of number of seed per plant and total seed weight per plant have larger dominance variance relative to their additive variance, indicating that genes controlling these traits have larger dominant effects, it is not suitable for the selection of single plant in offspring plants at the early stage of development, because these traits do not show up then. The alleles for traits of 1000 kernel weight and seed shell thickness have larger additive variance relative to their dominant variance, indicating that genes governing these traits have greater additive effects, with which the single plant can be selected in the progeny at the early stage of development. Although, the value of seed shell thickness has been shown to correlated positively with that of 1000 kernel weight, almost all the seeds of easily-shelled type are those with thin shell. However, ideal single plants with easily-shelled trait are those with intermediate phenotypes of seed shell thickness and 1000 kernel weight, by which the traits of large number of seeds per plant and total seed weight per plant could be selected. In the progeny population of this study, there were excellent single plants with high-yield and easily-shelled traits, of which the value of seed shell thickness was 0.17 mm (0.15 mm to 0.20 mm), the value of 1000 kernel weight was 14 g, the value of number of seeds per plant was 1137 and value of total seed weight per plant was 15.9 g. The results showed that taking the hybrid combinations of easily-shelled trait with the trait of seed shell thickness was the most effective selection indexes to breed the high-yield buckwheat varieties with the trait of easy shelling.